(untitled) (Communications in Mathematical Research, 2021)
In this paper, we study ∗-simple type A ω^2-semigroups in which D^∗ = D and D^∗|_E_S = M_d by the generalized Bruck-Reilly extension and obtain its structure theorem. We also obtain a criterion for isomorphisms of two such semigroups.